2003
DOI: 10.1002/etc.5620220222
|View full text |Cite
|
Sign up to set email alerts
|

Response of larval Xenopus laevis to atrazine: Assessment of growth, metamorphosis, and gonadal and laryngeal morphology

Abstract: Larval Xenopus laevis were exposed to one of four concentrations of atrazine (0, 1, 10, or 25 microg/L, 11 replicate tanks per treatment, 60-65 larvae per replicate) dissolved in an artificial pond water (frog embryo teratogenesis assay- Xenopus [FETAX]) medium beginning 48 h after hatching until the completion of metamorphosis. Separate groups of larvae (six replicate tanks per treatment, 60-65 larvae per replicate) were exposed to estradiol (100 microg/L), dihydrotestosterone (100 microg/L), or ethanol vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(42 citation statements)
references
References 40 publications
(66 reference statements)
6
33
2
Order By: Relevance
“…Based on findings of intersexuality at very low atrazine concentrations, Hayes et al (2002, 2003) concluded that the widespread use of atrazine may have been a significant factor in amphibian declines. However, a recent study (Carr et al 2003) indicated a higher threshold for atrazine-induced intersexuality in frogs. Additional research is needed to resolve this issue.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on findings of intersexuality at very low atrazine concentrations, Hayes et al (2002, 2003) concluded that the widespread use of atrazine may have been a significant factor in amphibian declines. However, a recent study (Carr et al 2003) indicated a higher threshold for atrazine-induced intersexuality in frogs. Additional research is needed to resolve this issue.…”
Section: Discussionmentioning
confidence: 97%
“…At much lower concentrations, atrazine in combination with nitrate reduced growth of X. laevis (Sullivan and Spence 2003). Hayes et al (2002, 2003) associated hermaphrodism and gonadal dysgenesis in amphibians with very low aquatic concentrations of atrazine (0.1 μg/L), whereas Carr et al (2003) observed significantly increased intersexuality only at higher concentrations (25 μg/L).…”
mentioning
confidence: 94%
“…Here are statements of two main findings from an industry-funded study (Carr et al, 2003). Notice that there are effects in one endpoint but no effects in the other:…”
Section: Confidence Levelsmentioning
confidence: 94%
“…On the other hand, studies finding no effects-all Syngenta funded-are represented as offering the final verdict on the matter. In the first Syngenta-funded study reporting no effects (Carr et al, 2003), references to the published studies reporting effects suggest conflict among the reports, which was not the case: "There have been conflicting reports regarding the potential for atrazine to influence reproductive development in amphibians at environmentally relevant concentrations" (Carr et al, 2003, p. 396). …”
Section: Incommensurate Reviews Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation